BRAND AND HERITAGE AKNOWLEDGEMENT - Lazuardi, Sofyan; Wibowo, Bambang Sri; Setyawan, Mochamad Ardi; Suprihandari, Miya Dewi (International Research of Multidisciplinary Analysis, 2023)
Kalimantan heritage is one of the many cultural assets owned by the Indonesian nation from hundreds of other cultures. One culture that is highly admired is the typical Kalimantan batik which is liked not only by native people of Kalimantan. However, it seems that these batik motifs have not been attached to the brands of each entrepreneur who produces them, the brands are only pinned by boutiques or small business entities that market them (Kapferer, J.-N., 2004). This needs to get support in the ease of processing and obtaining it for batik cloth production actors from the authorized agency. All of this needs to be done so that the works of local sons and daughters are protected from irresponsible parties. The wealth of Kalimantan batik motifs in general comes from the original motifs of the rich indigenous culture of Kalimantan. Based on several facts, it can be concluded that almost all original batik makers do not have personal brands for the batik works they have made and marketed. For this reason, it is necessary to provide an understanding of the importance of brands on patents for the creative ideas of batik motifs that they make by people who are experts in their fields (Keller, K.L. and Lehmann, DR, 2006).